Knowledge of Nurses Regarding Pain Management in the Patient Referring to the Emergency Departments of the Hospitals Affiliated to Iran University of Medical Sciences - J Mohammad Aliha; T Najafi Ghezeljeh; SH Haghani; SH Nasrollah Nejhad (Iran University of Medical Sciences, 2018)
Background & Aims: Nurses play a key role in the pain management of patients and must have adequate knowledge in this regard. The present study aimed to assess the knowledge of nurses regarding pain management in the patients referring to the emergency departments of the hospitals affiliated to Iran University of Medical Sciences. Materials & Methods: This descriptive, cross-sectional study was conducted on 150 emergency department nurses who were selected via census sampling in the hospitals affiliated to Iran University of Medical Sciences in 2018. The inclusion criteria were the minimum education level of master's degree and six months of work experience in the emergency department. Data were collected using the demographic questionnaire and the questionnaire of knowledge of pain management. Data analysis was performed in SPSS version 16 using descriptive statistics (frequency tables, mean, and standard deviation) and inferential statistics (Pearson's correlation-coefficient). Results: Mean age of the participants was 31.98±5.52 years. The majority of the nurses (82.9%) had no prior experience of pain management training. Regarding pain management in the emergency department, the mean score of knowledge was 37.055±11.53 out of 100. Conclusion: According to the results, the emergency department nurses had a low knowledge level regarding pain management. Therefore, provision of periodic training and pain assessment facilities and implementation of proper policies and methods for pain assessment could be effective in this regard. Moreover, our findings highlighted the need for training programs and retraining courses for the staff.